MUNICIPAL SOCIAL SERVICES. THE NEED FOR A REFOUNDATION - Miguel López-Cabanas (Papeles del Psicólogo, 2018)
The current municipal social services began to be implemented in the 1980’s. Largely descendants of the public beneficence that the local administrations provided in the past, they still display influences from that phase today. Confusion exists regarding their mission and their delimitation with other areas of social policy. There is an overload of bureaucratic and administrative work that limits the actions of the professionals of social intervention. It is necessary to refound the social services provided by the city councils, a process that should involve their reconceptualization as well as important normative, organizational and methodological changes.